DESAIN DIDAKTIS MATERI LUAS BANGUN DATAR DENGAN MODEL REALISTIC MATHEMATICS EDUCATION UNTUK MENGATASI HAMBATAN BELAJAR PADA PENALARAN MATEMATIS SISWA SEKOLAH DASAR - Syamsudin, Annisa Febrianti; Maulana, Maulana; Sudin, Ali (Jurnal Pena Ilmiah, 2019)
Mathematical reasoning ability of elementary school students is still undeveloped. This is evidenced by the results of learning obstacle tests conducted on fifth grade students of elementary school. Based on the results of learning obstacle tests, there are seven types of learning barriers related to mathematical reasoning. In addition, it also appears that students' resistance to two-dimensional figure. These problems encourage researchers to make an effort to solve problems by implementing Didactical Design Research based on the Realistic Mathematics Education. The purpose of this research is to detect learning obstacle, designing didactical design, implement didactical design, develop revised didactical design, implement didactical design revisions, and assess achievements of students' mathematical reasoning abilities. In each meeting, it consists of several activities that must be done or completed by students. The results of the implementation show that students' reasoning abilities in the two research subjects included in the high category.